Designing structurally ordered Pt/Sn nanoparticles in ionic liquids and their enhanced catalytic performance - Dietrich, Christine; Hähsler, Martin; Wang, Wu; Kübel, Christian; Behrens, Silke (ChemNanoMat, 2020)
Multimetallic nanoparticles (NPs) often exhibit enhanced catalytic properties that differ from their parent materials. Carefully exploring the structures of multimetallic NPs is a prerequisite for understanding the structure- and composition-associated properties. Herein, intermetallic Pt/Sn NPs with tunable compositions are designed exploiting the beneficial properties of ionic liquids (ILs) in a one-pot synthetic procedure. Metal salt precursors are reduced with triethylhydridoborate, whereby the cation of the triethylhydridoborate is adapted to the cation of the IL. Both the initial metal precursor ratio and the type of IL influence the structure of the NPs, with the effect of the IL being more pronounced. PtSn nanocrystals are obtained as phase pure products under optimized reaction conditions, whereby a microwave-assisted approach leads to higher crystallinity. In the hydrogenation of α,β-unsaturated aldehydes, the catalytic performance obviously depend on the NP composition. In bimetallic Pt/Sn NPs, higher Pt content leads to increased conversion, while increase in Sn increases selectivity to the cinnamic alcohol.
Online veröffentlicht: 21. Oktober 2020
Gesehen am 17.04.2024